Case Study: Engaging Learners Through Curiosity, Community, and a Sense of Exploration - Excell, Sarah; Huizenga, Erin (International Journal of Advanced Corporate Learning (iJAC), 2024)
This case study explores the collaboration between Smithsonian Affiliations and Desklight to develop a digital learning hub for Smithsonian’s Affiliates Program. Anchored in humancentered design, the design process relied heavily on ongoing insights from current Affiliates to identify the most useful information to share in this online resource. These insights guided the development of unique Learning Excursions within the learning hub that offered curated worksheets, real-world impact scenarios, and helped prospective Affiliates envision what it would look like to join forces with Smithsonian. The success of this learning hub is attributed to stakeholder involvement, personalized learning, real-world examples, flexible accessibility, community building opportunities, and a design thinking approach. This work serves as a blueprint for organizations aiming to enhance programs, foster meaningful engagement, and drive transformative outcomes by using learning as a benefit.